(3aGYdjI HQfGeL EQTGOj bGFe Ydi CfTWI GddYH dNaV GVWQGH GdSdhc GdeJMOj GdeYGQV dOi CWaGd GdQhVI (B/s - (3,QVhi ahRi Wg GdQjSs; (3YaGa GMeO YhjSs; (3LeGd eNJGQ MeRIs (2024)
(3gOaJ GdOQGSI GdMGdjI Edi GdJYQa Ydi aGYdjI HQfGeL EQTGOj bGFe Ydi CfTWI GddYH dNaV GVWQGH GdSdhc GdeJMOj GdeYGQV dOi CWaGd GdQhVI hGdJYQa Ydi eOi GSJeQGQ aGYdjI GdHQfGeL HYO eQhQ TgQ ef JWHjbg NdGd GdJbjje GdJJHYj hJMbjkbG dgPG GdgOa abO JchfJ YjfI GdOQGSI ef YOO (B(6) (3CWaGd ef GdPchQ hJQGhMJ CYeGQge ef (B(5-7)(3SfhGJ hWHbJ GdHGMKI GdCOhGJ GdJGdjI(B: (3ebjGS GVWQGH GdJMOj GdeYGQV EYOGO eLOj GdOShbj, HQfGeL EQTGOj bGFe Ydi CfTWI GddYH(B((3EYOGO GdHGMKI(B)(3, GSJeGQI OQGSI GdMGdI EYOGO GdHGMKI(B). (3hCSaQJ GdfJGFL Yf Cfg(B: (3JhLO aQhb PGJ OdGdI EMUGFjI Hjf eJhSWj QJH OQLGJ CWaGd GVWQGH GdJMOj GdeYGQV (B((3GdeLehYI GdJLQjHjI(B) (3aj GdbjGSjf GdbHdj hGdHYOj Ydi ebjGS GVWQGH GdJMOj GdeYGQV dUGdM GdbjGS GdHYOjhdGJhLO aQhb PGJ OdGdI EMUGFjI Hjf eJhSWj QJH OQLGJ CWaGd GVWQGH GdJMOj GdeYGQV (B((3GdeLehYI GdJLQjHjI (B) (3aj GdbjGSjf GdHYOjhGdJJHYj HYO eQhQ TgQ ef GfJgGA JWHjb GdHQfGeL Ydi ebjGS GVWQGH GdJMOj GdeYGQV hCHYGOg(B.s
The current study aimed to identify The Effectiveness of a counseling program based on play activities to reduce oppositional defiant disorder in kinder garden children and to determine the extent of the continuity of the effectiveness of the program after one month of its implementation during the follow- up evaluation to achieve this goal the study sample consisted of 6 male children, ages (5-7) years. the re-searcher applied the following tools: the scale of oppositional defiant disorder preparing by Mahdy EL- Desouki, and a counseling program based on play activities by the researcher and the case study form , pre-pared by the researcher .The results revealed that there are statistically significant differences between the mean scores of the oppositional challenge disorder children the experimental group, in the pre and post measurements on the oppositional challenge disorder scale in favor of the post measurement.There are no statistically significant differences between the mean scores of the oppositional challenge disorder children the experimental group, in the post and follow- up measurements after one month of applying the program.Keywords: oppositional defiant disorder- play activities- kinder garden children- a counseling program.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B113-118.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3QjGV GdGWaGds; (3GVWQGH GdJMOj GdeYGQV s -- (3CfTWI GddYHs -- (3CWaGd GdQhVIs